أثر المعنى في تعدد وجوه الإعراب عند أبي جعفر النحاس : دراسة تطبيقية في سورة المائدة - علي، عبدالعزيز موسى درويش; طافش، رائد فريد نجيب; أبو الرب، محمد عبدالله صالح (جامعة الجنان - مركز البحث العلمي, 2011)
تناولت الدراسة العلاقة بين المعنى وتعدد وجوه الإعراب في القرآن الكريم، وأخذت الدراسة إعراب سورة المائدة من كتاب إعراب القرآن لأبي جعفر النحاس نموذجاً تطبيقياً للوقوف على هذه العلاقة، فحصرت الآيات التي اختلف العلماء في إعرابها، وذكرت وجوه الإعراب المتعددة وناقشتها في ضوء المعنى المترتّب على هذا الخلاف، فتبيّن أن المعنى هو العامل الأبرز في تعدد وجوه الإعراب في كثير من مواضع الخلاف في إعراب السورة الكريمة The semantic impact on the diversity of parsing according to Abi- Ja'far ANNaḥaas: \ An applied study on Surat Al Ma'idah (The Repast) \ The current paper studies the relationship between the meaning and its various parses in the holy Qura'n. The study has taken the parsing moods of Chapter 5 (Surat) Al Ma'idah (The Repast) from the book named 'i9raab Al-Quran' by Abi Ja'far Al-Naḥaas as a typical example of application to demonstrate this relation. First, the parsing forms of controversial verses in chapter 5 were confined. The diversity of perspectives of parsing these forms among scholars were discussed in light of the meaning resulted of their disputes. Findings revealed that the meaning is the prominent factor causes the diversity of parsing in the disputed positions (situations) of Surat Al Ma'idah.
Keywords: اسرار القرآن -- إعراب القرآن -- معاني القرآن -- سورة المائدة -- كتاب إعراب القرآن -- التفاسير -- ألفاظ القرآن